2012
DOI: 10.1103/physrevlett.108.263001
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Three-Body Parameter Universality in Efimov Physics

Abstract: In recent years extensive theoretical and experimental studies of universal few-body physics have led to advances in our understanding of universal Efimov physics. Whereas theory had been the driving force behind our understanding of Efimov physics for decades, recent experiments have contributed an unexpected discovery. Specifically, measurements have found that the so-called threebody parameter determining several properties of the system is universal, even though fundamental assumptions in the theory of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
315
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(352 citation statements)
references
References 39 publications
35
315
1
1
Order By: Relevance
“…Efimov states may be considered to be supported by an effective adiabatic potential that is a function of the hyperradius R. For a zero-range two-body potential with large scattering length a, this potential is attractive and proportional to R −2 for R |a| [44] and supports an infinite number of bound states as a → ±∞. For potential curves with long-range van der Waals tails, however, Wang et al [29] have shown that the effective adiabatic potential reaches a minimum and then rises to a wall or barrier near R = 2r vdW . The positions of the minimum and wall depend to some extent on the details of the two-body potential and the number of bound states it supports but become nearly universal as the number of two-body bound states increases.…”
Section: Three-body Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Efimov states may be considered to be supported by an effective adiabatic potential that is a function of the hyperradius R. For a zero-range two-body potential with large scattering length a, this potential is attractive and proportional to R −2 for R |a| [44] and supports an infinite number of bound states as a → ±∞. For potential curves with long-range van der Waals tails, however, Wang et al [29] have shown that the effective adiabatic potential reaches a minimum and then rises to a wall or barrier near R = 2r vdW . The positions of the minimum and wall depend to some extent on the details of the two-body potential and the number of bound states it supports but become nearly universal as the number of two-body bound states increases.…”
Section: Three-body Parametermentioning
confidence: 99%
“…However, in atomic systems it has been found experimentally [13,27] that the 3BP is nearly constant when expressed in terms of the van der Waals length r vdW [6], which quantifies the dispersion interaction between two neutral atoms. We refer to this feature of Efimov physics as van der Waals universality of the 3BP, and it has been the subject of a number of theoretical investigations [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…This is assured through a parameter, the three-body hard core R 0 , that bounds from below the energies of the Efimov states. In cold-atom systems, this parameter is on the order of the van der Waals length l vdW [17][18][19] . Experimental coldatom systems are metastable, and particles disappear from the trap into deeply-bound states via the notorious three-body losses.…”
mentioning
confidence: 99%
“…Some recent theoretical works have addressed the corrections coming from the finite range of inter-atomic potentials in the coordinate-space formalism (Thøgersen et al 2008b, Thøgersen, Fedorov, Jensen, Esry & Wang 2009, Wang, D'Incao & Esry 2011, Sørensen et al 2011) and using momentum-space effective field theory (Massignan & Stoof 2008, Platter et al 2009, Ji et al 2010, Naidon et al 2012. In particular, the study of (Massignan & Stoof 2008) provide results that are close to the experimental data.…”
Section: Measurable Consequences In Physics Systemsmentioning
confidence: 70%
“…This implies that there is some generic universality even in the three-body parameter which cannot be captured by simple zero-range models that need the ρ 0 supplied from elsewhere. A number of theoretical works have presented various models that explain the observations (Naidon et al 2012, Chin 2011, Wang, D'Incao, Esry & Greene 2012, Schmidt et al 2012 and it seems clear that the two-body inter-atomic potential is the culprit since it has a large repulsion at short distance which will naturally provide a threebody cut-off (Sørensen et al 2012a, Sørensen et al 2012b. However, there is still a question of how the number of bound two-body states in the inter-atomic potential influences a − (Wang, D'Incao, Esry & Greene 2012, Sørensen et al 2012a).…”
Section: New Directionsmentioning
confidence: 99%